Safety climate factors at selected chemical manufacturing plant in Malaysia - Junaidah, Zakaria; Che Rosmani, Che Hassan; Mahar Diana, Hamid; Ezrin Hani, Sukadarin (American Institute of Chemical Engineers, 2019)
Statistics in Malaysia show accident cases in the manufacturing industry is the highest as compared to another sector. The concept of safety climate gained interest in many industries as a means of reducing accident. This study assessed workers' perceptions toward safety climate factors, Management commitment, communication, a priority of safety, safety rules procedures, social environment, supportive environment, involvement, personal priorities and need for safety, personal appreciation of risk, physical work environment, and lastly top management's commitment and priority. Safety Climate Assessment Toolkit and Zohar Safety Climate Questionnaires were used in this study. A cross-sectional sample of 309 workers participated. Lowest total mean score was for a personal appreciation of risk (M = 5.41, SD = 1.03), supportive environment (M = 6.61, SD = 0.82), and physical work environment (M = 6.74, SD = 1.24). There was a significant difference between production and nonproduction workers for their perceptions toward involvement in safety (Z = 15.579, P < .001). From the correlation test, age, gender, education level, shift work, and the group were significantly correlated with the nine dimensions of safety climate. Lastly, workers' perception of how management prioritized safety is generally good. A total mean score is (4.89) from the 16 items of Zohar safety climate questionnaire which covers declarative, proactive, and active practices of their management.